Women in the Lab, Men in the Field? Correlations between Gender and Research Topics at Three Major Archaeology Conferences. - Chen, Yichun; Marwick, Ben (Journal of Field Archaeology, 2023)
Rising interest in gender equality in society has resulted in greater scrutiny of gender inequality in academic communities. Analysis of authorship of peer-reviewed publications shows that archaeology, like other academic fields, has long been dominated by men. We ask if gender disproportionality is evident in the topics presented by archaeologists at major conferences, particularly the Society of American Archaeology (SAA), the European Association of Archaeologists (EAA), and the Computer Applications and Quantitative Methods in Archaeology (CAA) meetings. Does participants' gender correlate with the topics of their presentations? We analyzed presenters' names in published programs to infer gender. We used machine learning to identify topics from presentation titles. We found distinctive topics that are strongly associated with women, such as cultural heritage, GIS, and isotope analyses. Awareness of these correlations between research topics and gender is important to ensure equitable participation in archaeology and unbiased access to training opportunities for students.